Nilai-Nilai Pendidikan Akhlak Dalam Novel Children Of Heaven Karya Enang Rokajat Asura - Rahmad Hulbat (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
This research is a qualitative research (library research). This study examines the values ​​of moral education in the novel children of heaven by Enang Rokajat Asura. The purpose of this study is to describe the values ​​of moral education in the novel children of heaven, including the value of moral education to Allah SWT and the value of moral education to fellow humans. The data sources of this research are the novel children of heaven by Enang Rokajat Asura and various literatures related to the object of research. The data collection technique used the library research method, namely in the form of data collection techniques that were not directly aimed at the research subject, but through several books, magazines, journals, pamphlets, and other relevant documentary materials in the research. The results showed that several values ​​of moral education were found in the novel children of heaven by Enang Rokajat Asura which include; 1) The values ​​of moral education to Allah SWT are obedience, trustworthiness, gratitude, and patience. 2) The values ​​of moral education to fellow human beings are love, responsibility, and help.